Une posture de déresponsabilisation énonciative. L’ethos du Dr. Cottard - Anna Jaubert (Corela, 2020)
The examination of enunciative postures provides a decisive insight into pragmatic studies. Indeed, acts of language cannot be abstracted from the enunciative conditioning that underlies their emergence, to the extent that we are now increasingly talking about an enunciativo-pragmatic approach (rather than a “pragma-enunciative” one, in order to reflect the operative order). This approach has made stylistics operating again by reintroducing the subject into its statements on a linguistic basis. In this field, Alain Rabatel’s work has produced a series of key concepts with a high heuristic performance for instance the concept of enunciative posture, and specially the opposition between over-enunciation and under-enunciation. This article analyses various cases of denial of enunciative responsibility that Frédéric Berthet once described as "Cottard Syndrome”, which is characterized by a permanent under-assertion. The point is that this verbal behaviour exploits the enunciative reflexivity of meta-enunciation as a "blank talk", and links it with some postural indices of non-seriousness to shut down any illocutionary value.